Efficacy of neratinib in the treatment of HER2/neu-amplified epithelial ovarian carcinoma in vitro and in vivo - Menderes, Gulden (Med Oncol, 2017)
Epithelial ovarian carcinoma is the most lethal of gynecologic malignancies. There is a need to optimize the currently available treatment strategies and to urgently develop novel therapeutic agents against chemotherapy-resistant disease. The objective of our study was to evaluate neratinib’s preclinical efficacy in treating HER2-amplified ovarian cancer. Neratinib’s efficacy in treating HER2-amplified ovarian cancer was studied in vitro utilizing six primary tumor cell lines with differential HER2/neu expression. Flow cytometry was utilized to assess IC(50), cell signaling changes, and cell cycle distribution. Neratinib’s in vivo efficacy was evaluated in HER2-amplified epithelial ovarian carcinoma xenografts. Three of six (50%) ovarian cancer cell lines were HER2/neu-amplified. Neratinib showed significantly higher efficacy in treating HER2/neu-amplified cell lines when compared to the non-HER2/neu-amplified tumor cell lines (mean ± SEM IC(50):0.010 μM ± 0.0003 vs. 0.076 μM ± 0.005 p < 0.0001). Neratinib treatment significantly decreased the phosphorylation of the transcription factor S6, leading to arrest of the cell cycle in G0/G1 phase. Neratinib prolonged survival in mice harboring HER2-amplified epithelial ovarian carcinoma xenografts (p = 0.003). Neratinib inhibits proliferation, signaling, cell cycle progression and tumor growth of HER2-amplified epithelial ovarian carcinoma in vitro. Neratinib inhibits xenograft growth and improves overall survival in HER2/neu-amplified ovarian cancer in vivo. Clinical trials are warranted.